2021
DOI: 10.1080/10717544.2021.1979131
|View full text |Cite
|
Sign up to set email alerts
|

Crotamiton-loaded tea tree oil containing phospholipid-based microemulsion hydrogel for scabies treatment: in vitro , in vivo evaluation, and dermatokinetic studies

Abstract: Crotamiton (CRT) is a commonly approved drug prescribed for the scabies treatment in many countries across the globe. However, poor aqueous solubility and low bioavailability, and side effects restrict its use. To avoid such issues, an appropriate carrier system is necessary which can address the aforementioned challenges for attaining enhanced biopharmaceutical attributes. The current study intends to provide a detailed account on the development and evaluation of CRT-loaded microemulsion (ME) hydrogel formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The optical photomicrographs showed that the liposomes had a consistent vesicular shape, homogeneity, and no aggregation was observed (as shown in Figure A). Thus, this finding is supported with the similar findings observed in the published literature …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The optical photomicrographs showed that the liposomes had a consistent vesicular shape, homogeneity, and no aggregation was observed (as shown in Figure A). Thus, this finding is supported with the similar findings observed in the published literature …”
Section: Resultssupporting
confidence: 93%
“…Both selected excipients are to play an important role in the development of liposomes. The higher solubility of the drug in lipids and solvents is an important consideration in topical permeation and drug deposition into the skin …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro drug release for HP was determined by using a dialysis method as per the procedure described in the literature. The dialysis tube (MWCOs 14 kD, Sigma, USA) was pretreated in distilled water at least overnight prior to performing the drug release study. The optimized LCNP formulation (HP5) equivalent to 20 mg of HP and pure drug (20 mg) taken in the dialysis tube were suspended in the SGF (pH 1.2) and SIF (pH 6.8) containing 2% IPA and kept under stirring at 100 rpm on a water shaker bath maintained at 37.0 ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The method of preparation was based on the aqueous titration method, under magnetic stirring at 900 rpm. It was adapted to the experimental conditions, including in this case, a short period of heating, under a controlled temperature, at 70 • C. Chen L. et al, reported the use of heating in their preparation step to support a better homogenization of samples [72]. In such a way, in our study, heating was helpful to assure the melting of lecithin and its homogenization with the oil phase and further components.…”
Section: Preparation Of Salicylic Acid-based Microemulsionsmentioning
confidence: 96%